Selected aspects of early childhood education and primary education in the Slovak Republic during the period of transformation of the Slovak education system - Iveta Kovalčíková; Juraj Kresila; Monika Miňová (Ignatianum University Press, 2019)
The aim of this contribution is to assess selected aspects of the development of early childhood education and primary education in the Slovak Republic (SR) during the last twenty years in the context of the process of the transformation of the Slovak education system. Our aim is to emphasise: 1. the formation of a legislative framework for education reforms in SR; and 2. the development of a curriculum for early childhood and primary education. The contribution outlines various mechanisms for curricular transformation which are dependent on mutual conpgurations and the characteristic components of this diocult process. In the contribution we name the basic factors determining the conditions for the preparation, the implementation process and the assessment of results of education reform in early childhood and primary education. At the end of the article we oner suggestions which we feel could lead to the successful modipcation or further implementation of education reform in the Slovak Republic.